Health economics for treatment of diabetic foot ulcers: a cost-effectiveness analysis of eight skin substitutes. (1st September 2019) - Samsell, Brian; McLean, Julie; Cazzell, Shawn; Dorsch, Kimberly; Moyer, Peter M.; Moore, Mark
Abstract : Aim: Skin substitutes are frequently used to treat chronic diabetic foot ulcers (DFU), and many different options are available. While the clinical efficacy of many products has been evaluated, a comprehensive cost-effectiveness analysis comparing the most popular skin substitutes and using the most recent cost data has been lacking. Methods: This study compared eight skin substitutes using published efficacy rates combined with the Centers for Medicare and Medicaid Services (CMS) 2018 cost data. The study criteria resulted in the inclusion of seven studies that described efficacy rates for treatment of DFUs using the skin substitutes. Results: The results revealed wide discrepancies between these skin substitutes for the costs of treatments and healing rates in hospital outpatient departments and physician office settings. Healing rates for 12 and 16 weeks ranged from 28% to 68%, while the average cost for treating one DFU varied from 2001 to 14, 507 and 1207 to 8791 in the hospital outpatient department and physician's office setting, respectively. The estimated patient share of costs for treating a single DFU ranged from 400 to 2901 and 241 to 1758 in the hospital outpatient department and physician's office setting, respectively. Most importantly, the estimated number of wounds healed out of 100 DFUs per 1000 expenditure with each patient ranged from 3.9–26.5 DFUs in the hospital outpatient department, and 4.3–36.4 DFUs in the physicians' office setting. Conclusions: This study revealed that the costs of a skin substitute itself did not necessarily correlate with its healing efficacy. These results provide a comprehensive cost-effectiveness analysis to enable integrated health-care systems, health professionals and reimbursement payers to make informed value decisions when treating DFUs.